Sarcolemmal ATP-sensitive potassium channel protects cardiac myocytes against lipopolysaccharide-induced apoptosis - Zhang, Xiaohui (Int J Mol Med, 2016)
The sarcolemmal ATP-sensitive K(+) (sarcK(ATP)) channel plays a cardioprotective role during stress. However, the role of the sarcK(ATP) channel in the apoptosis of cardiomyocytes and association with mitochondrial calcium remains unclear. For this purpose, we developed a model of LPS-induced sepsis in neonatal rat cardiomyocytes (NRCs). The TUNEL assay was performed in order to detect the apoptosis of cardiac myocytes and the MTT assay was performed to determine cellular viability. Exposure to LPS significantly decreased the viability of the NRCs as well as the expression of Bcl-2, whereas it enhanced the activity and expression of the apoptosis-related proteins caspase-3 and Bax, respectively. The sarcK(ATP) channel blocker, HMR-1098, increased the apoptosis of NRCs, whereas the specific sarcK(ATP) channel opener, P-1075, reduced the apoptosis of NRCs. The mitochondrial calcium uniporter inhibitor ruthenium red (RR) partially inhibited the pro-apoptotic effect of HMR-1098. In order to confirm the role of the sarcK(ATP) channel, we constructed a recombinant adenovirus vector carrying the sarcK(ATP) channel mutant subunit Kir6.2AAA to inhibit the channel activity. Kir6.2AAA adenovirus infection in NRCs significantly aggravated the apoptosis of myocytes induced by LPS. Elucidating the regulatory mechanisms of the sarcK(ATP) channel in apoptosis may facilitate the development of novel therapeutic targets and strategies for the management of sepsis and cardiac dysfunction.